2007
DOI: 10.1007/s00464-005-0448-3
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for hand-assisted laparoscopic colectomy: a single surgeon’s experience

Abstract: Approximately 21 to 25 cases were needed to achieve proficiency in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
(22 reference statements)
1
25
0
Order By: Relevance
“…This is in contrast to the lower number reported for technical competency. 13,14 In the present study, the overall operative duration as a primary end point declined by 78 minutes (PϽ.001) in P2. The overall morbidity, infectious complications, length of stay, and readmission rate were also lower in P2.…”
Section: Commentmentioning
confidence: 81%
“…This is in contrast to the lower number reported for technical competency. 13,14 In the present study, the overall operative duration as a primary end point declined by 78 minutes (PϽ.001) in P2. The overall morbidity, infectious complications, length of stay, and readmission rate were also lower in P2.…”
Section: Commentmentioning
confidence: 81%
“…As a result, possible statistic errors arising from different endoscopists, different procedures, different operation settings, and different medical centers were eliminated [6]. Moreover, we divided the patients into two groups, the easy group and the difficult group, according to the level of operation difficulty [7]. To ensure reliability of the statistical results, we used the chi-square test to eliminate possible interference from different conditions of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that clinical outcomes improve when surgeons develop their own expertise in their procedure, and have indicated the presence of a learning curve for their surgical procedures [10,11,12]. There has been some published studies investigating the presence of a learning curve for phacoemulsification which has become the method of choice for cataract surgery [13,14,15].…”
Section: Discussionmentioning
confidence: 99%